Microstructured Multilevel Bacterial Cellulose Allows the Guided Growth of Neural Stem Cells. Issue 39 (24th August 2016) - Geisel, Natalie; Clasohm, Jasmin; Shi, Xudian; Lamboni, Lallepak; Yang, Junchuan; Mattern, Kamil; Yang, Guang; Schäfer, Karl‐Herbert; Saumer, Monika
Abstract : Repeated photolithographic and etching processes allow the production of multileveled polymer microstructures that can be used as templates to produce bacterial cellulose with defined surfaces on demand. By applying this approach, the bacterial cellulose surface obtains new properties and its use for culturing neural stem cells cellulose substrate topography influences the cell growth in a defined manner.